On a knife-edge : the poetry of João Cabral de Melo Neto - Brandellero, Sara Lucia Amelia, 1967- (Oxford modern languages and literature monographs., 2011)
'On a Knife-Edge' represents the first book-length study in English solely devoted to the work of Joao Cabral de Melo Neto (1920-1999), one of Brazil's foremost poets of the 20th century and a unique voice within Brazilian Modernism.